Gender Politics and Sexuality: Indonesian Transgender in the Context of Indonesia and Western Europe Society - Tanti Noor Said (Jurnal Perempuan, 2015)
This paper attempts to analyze how Indonesian gay males and transgenders male to female in two different social, cultural and political contexts (in Indonesia and Northern Europe) are actively engaged in the making of their own subjectivity. Their subjectivities are entangled with gender, sexuality, religion, romantic love relationships and kinship. They juggle in negotiating and making sense of norms and values of societies that projected towards them. This paper aims to shed light on gender politics of gay and transgender Indonesians in the context of heterosexual hegemony and migration.